2020
DOI: 10.1088/2057-1976/ab6fb7
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic modulation of cortical neurons using organic light emitting diodes (OLEDs)

Abstract: Objective -There is a need for low power, scalable photoelectronic devices and systems for emerging optogenetic needs in neuromodulation. Conventional light emitting diodes (LEDs) are constrained by power and lead-counts necessary for scalability. Organic LEDs (OLEDs) offer an exciting approach to decrease power and lead-counts while achieving high channel counts on thin, flexible substrates that conform to brain surfaces or peripheral neuronal fibers. In this study, we investigate the potential for using OLED… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Optogenetics is the induction of light-sensitive molecules in cells to allow for modulation of the cell’s activity . As such, OLEDs have been used to optogenetically control different neuronal populations. Another promising area of work for neuronal modulation is the use of organic optoelectronic materials. Different studies have shown the propensity to initiate neural firing through optoelectronic photostimulation ,,,, or even silencing .…”
Section: Interfacing Organic Bioelectronics With Cellsmentioning
confidence: 67%
“…Optogenetics is the induction of light-sensitive molecules in cells to allow for modulation of the cell’s activity . As such, OLEDs have been used to optogenetically control different neuronal populations. Another promising area of work for neuronal modulation is the use of organic optoelectronic materials. Different studies have shown the propensity to initiate neural firing through optoelectronic photostimulation ,,,, or even silencing .…”
Section: Interfacing Organic Bioelectronics With Cellsmentioning
confidence: 67%
“…Optogenetic stimulation of cortical neurons in culture and in vivo was also investigated by Sridharan et al using simultaneous read-out of neuronal activity via microelectrode arrays. [252] For this, blue and green OLEDs on PET substrates were used, which reached power densities exceeding 1 mW mm −2 when driven in pulsed mode at 10 Hz/10 ms at voltages of 12.5 V (blue OLEDs) and 15 V (green OLEDs).…”
Section: Oleds For Optogeneticsmentioning
confidence: 99%
“…[ 67 ] With the inherent advantages like flexibility, biocompatibility, and adjustable dimensions, recently reported low power OLEDs also integrated with neural tissues and interact with genetically engineered light‐sensitive opsins. [ 68 ] We envision that there will be more investigations about the development of OLED‐based implantable systems for biomedical applications in the future research.…”
Section: Electroluminescence Materials and Devicesmentioning
confidence: 99%